ANALISIS PENGARUH CAPITAL, INEFISIENSI, DANA PIHAK KETIGA DAN SIZE TERHADAP NON PERFORMING LOAN PADA BANK UMUM KONVENSIONAL - Rizal, Ahmad; Taswan, Taswan (Proceeding SENDI_U, 2020)
This study aims to provide information about the analysis of the influence of CAPITAL, INFFICIENCY,DEPOSIT, and SIZES with NPL ratios on commercial banks in Indonesia in the 2016-2018. The data usedsecondary data from the Annual Report of a bank that has met the sample criteria (purposive sampling). Thesample, which is used, in, research, is a number of, 41, commercial banks listed on the IDX. The analyticalmethod used in this study is multiple linear regression and the classic assumption test.The results show. Capital has a negative effect and. significant to. Non-Performing Loans (NPL), whileInefficiency has positive and significant effects, deposit and Size do not. has a significant influence on NonPerforming Loans (NPL). The predictive ability of these variables in explaining Non-Performing Loans (NPL)of 50.7.% while the remaining 49.3.% is explained by other variables outside this study